How effective is tetracaine 4% gel, before a venipuncture, in reducing procedural pain in infants: a randomized double-blind placebo controlled trial - Sherlock Rebecca; Gaboury Isabelle; Hogan Debora L; Lemyre Brigitte; Blanchard Colline; Moher David (BMC, 2007)
Abstract Background Procedural pain relief is sub-optimal in neonates. Topical tetracaine provides pain relief in children. Evidence of its efficacy and safety in neonates is limited. The objective of this study was to assess the efficacy and safety of topical tetracaine on the pain response of neonates during a venipuncture. Methods Medically stable infants greater than or equal to 24 weeks gestation, requiring a venipuncture, were included. Following randomization and double blinding, 1.1 g of tetracaine or placebo was applied to the skin for 30 minutes. Participants received oral sucrose if they met local eligibility criteria. The venipuncture was performed according to a standard protocol. A medium effect size in the pain score (corresponding to about 2 point difference in the PIPP score) was considered clinically significant, leading to a sample size of 142 infants, with 80% statistical power. Local skin reactions and immediate adverse cardiorespiratory events were noted. The primary outcome, PIPP score at 1 minute, was analysed using an independent Student's t-test. Results One hundred and forty two infants were included, 33 +/- 4 weeks gestation, 2100 +/- 900 grams and 6 +/- 3 days of age. There was almost no difference in PIPP scores at 1 minute between groups (mean difference -0.09; 95% confidence interval [CI]: -1.68 to 1.50; P = . 91). Similarly, there were no differences in PIPP scores during the 2nd, 3rd and 4th minute. Duration of cry did not differ between the groups (median difference, 0; 95% CI, -3 to 0; P = . 84). The majority of infants in both groups received sucrose 24%. Sucrose had a significant effect on the PIPP score, as assessed by an ANOVA model (p = 0.0026). Local skin erythema was observed transiently in 11 infants (7 in the tetracaine and 4 in the placebo group). No serious side effect was observed. Conclusion Tetracaine did not significantly decrease procedural pain in infants undergoing a venipuncture, when used in combination with routine sucrose administration.